2016
DOI: 10.1589/jpts.28.2232
|View full text |Cite
|
Sign up to set email alerts
|

The effect of <i>Monkey Chair and Band</i> exercise system on shoulder range of motion and pain in post-stroke patients with hemiplegia

Abstract: [Purpose] A simple rehabilitation device system for strengthening upper limb muscles in hemiplegic patients was developed. This system, which stimulates active exercise while accounting for intensity, time, and frequency, was examined in the present pilot study. [Subjects and Methods] Patients had shoulder pain and limited shoulder movement. Changes in range of motion (ROM) and scores of a visual analog scale (VAS) for pain were evaluated in the experimental and control groups every four weeks for twelve weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Slow-stroke massage trials either do not use a clear pain scale, 88 or were not compared with placebo or usual therapy. 35,89,90 No systematic reviews were identified for robotic-assisted physical therapy, 91 cryotherapy, 92 extracorporeal shockwave therapy, 93 inferential current therapy, 94,95 repetitive transcranial magnetic stimulation, 96 hyaluronic acid injection, 67 suprascapular nerve block, 97 segmental neurotherapy 98 or other pharmacological therapies such as gabapentin, and therefore a SR looking specifically at these interventions may be worth undertaking. The EBRSR covers studies for stroke rehabilitation including hemiplegic shoulder pain that are not included in existing systematic reviews.…”
Section: Discussionmentioning
confidence: 99%
“…Slow-stroke massage trials either do not use a clear pain scale, 88 or were not compared with placebo or usual therapy. 35,89,90 No systematic reviews were identified for robotic-assisted physical therapy, 91 cryotherapy, 92 extracorporeal shockwave therapy, 93 inferential current therapy, 94,95 repetitive transcranial magnetic stimulation, 96 hyaluronic acid injection, 67 suprascapular nerve block, 97 segmental neurotherapy 98 or other pharmacological therapies such as gabapentin, and therefore a SR looking specifically at these interventions may be worth undertaking. The EBRSR covers studies for stroke rehabilitation including hemiplegic shoulder pain that are not included in existing systematic reviews.…”
Section: Discussionmentioning
confidence: 99%
“…In order to quantify subtle changes during e.g., rehabilitation it is important, however, to extend the information extracted from the finger-to-nose task beyond cycle time [ 13 ]. Shoulder ROMs, reliably assessed in the present study, have been shown to be valuable in the treatment and diagnosis of neurological disorders, e.g., in a group of patients with stroke impairments, shoulder FE/AbAd were used to show improvements after training with a specific rehabilitation device (change in FE: ~35° and Ab-Ad: ~23°) [ 35 ]. Shoulder ROMs were also used to investigate upper limb mobility in patients with different types of spinal cord injuries [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…One RCT by Costantino et al ( 31 ) including 32 patients with stroke found that the subjects who underwent voluntary isometric muscle contraction in upper extremities with and without vibrations for 4 weeks reported decreased pain (Level of evidence II). According to another RCT ( 32 ) on 12 post-stroke patients, the participants who did joint motion and strengthening training via a specific exercise tool experienced less pain than the participants without intervention at 4, 8, and 12 weeks (Level of evidence II). Similarly, a RCT ( n = 40) pointed out that 3-week neuromuscular joint facilitation combined with acupuncture can reduce post-stroke pain more than 3-week pure acupuncture therapy ( 33 ) (Level of evidence II).…”
Section: Resultsmentioning
confidence: 99%